Oncoming traffic - Manaka, Maakomele R (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2016)
The poems in my collection Oncoming Traffic mainly look at the silence in my personal conflicts. Fusing different styles and tones of writing from the lyrical to the surreal, these poems grapple with issues I struggle with on a daily basis. First as a man, second as a man with a physical disability, and lastly as a black man dealing with the reality of living in a dysfunctional/disabled society. The silence in my personal conflicts means, writing what I cannot say, stripping myself bare and vulnerable. My inspiration has come from poets who articulate such silences.
Keywords: Uncatalogued